Taxonomic status and phylogenetic relationships of the desert monitor Varanus griseus caspius (Squamata: Varanidae) from the territory of Uzbekistan - Kuchboev, Abdurakhim E.; Amirov, Oybek O.; Yuldoshxonov, Azamat A.; Shapaotov, Ruziboy K.; Raxmatullayev, Baxodir A.; Abduraupov, Timur V. (Acta Biologica Sibirica, 2025)
This study investigates the phylogenetic position and genetic diversity of Varanus griseus caspius, a widely distributed yet understudied subspecies of monitor lizard in Central Asia, with a focus on samples collected from Uzbekistan. Using DNA barcoding based on the mitochondrial cytochrome oxidase subunit I (COI) gene, molecular phylogenetic analyses were conducted via Maximum Likelihood (ML) and Bayesian Inference (BI) approaches. In addition, genetic distance and Disparity Index analyses were employed to assess evolutionary relationships among Varanus species. The V. g. caspius specimens formed a highly supported clade with V. griseus sequences in GenBank, indicating a close genetic affinity and confirming its subspecies status. Genetic distance values and substitution pattern similarities further revealed minimal divergence between V. g. caspius and other V. griseus lineages, suggesting recent common ancestry and ongoing gene flow. In contrast, significantly greater divergence was observed between V. g. caspius and other Varanus species. These findings clarify the phylogenetic placement of V. g. caspius within the V. griseus complex and provide essential baseline data for future taxonomic and conservation efforts.